From political economy analysis to doing development differently: a learning experience - Booth, David; Harris, Daniel; Wild, Leni (ODI, 2016)
A study of how development efforts can be strengthened by an awareness of political economy, reflecting on the experiences of PoGo policy researchers.
Keywords: IMPORTANT

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT